Carbon monoxide dehydrogenase from Rhodospirillum rubrum. - Bonam, D (1984)
The carbon monoxide dehydrogenase from the photosynthetic bacterium Rhodospirillum rubrum was purified over 600-fold by DEAE-cellulose chromatography, heat treatment, hydroxylapatite chromatography, and preparative scale gel electrophoresis. In vitro, this enzyme catalyzed a two-electron oxidation of CO to form CO2 as the product. The reaction was dependent on the addition of an electron acceptor. The enzyme was oxygen labile, heat stable, and resistant to tryptic and chymotryptic digestion. Optimum in vitro activity occurred at pH 10.0. A sensitive, hemoglobin-based assay for measuring dissolved CO levels is presented. The in vitro Km for CO was determined to be 110 microM. CO, through an unknown mechanism, stimulated hydrogen evolution in whole cells, suggesting the presence of a reversible hydrogenase in R. rubrum which is CO insensitive in vivo.